Criterion-Level Characteristics of the Formation of the Performing Culture of Future Piano Teachers - Mykhaliuk, Alla (Educological discourse, 2023)
The article presents a criterion-level characteristic of the formation of the performance culture of future piano teachers, which is an indicator of the perfect instrumental and performance training of applicants to higher artistic education. The research was conducted using the methods of theoretical generalisation, comparative analysis and synthesis, on the basis of which the criteria, indicators and levels of formation of the performing culture of future piano teachers at higher educational institutions were identified and substantiated. The ways of pedagogical diagnostics of the formation of the performing culture of future piano teachers are revealed. Criteria and indicators of this phenomenon are described. The levels of formation of the performing culture of future piano teachers are outlined, namely: creative, competent, normative, adaptive. The methods of measuring the indicators of the formation of the performing culture of future piano teachers at each stage of the confirmatory experiment presented in the study are substantiated. The conditional definition of the criteria, indicators, levels and methods of the formation of the performing culture of future piano teachers allows to assess the state of the studied quality of master students in the process of the confirmatory experiment, as well as to create a reliable basis for the organisation of further research work on the modernisation of the ways of pedagogical support in the process of performing and instrumental training of applicants to higher art education in order to form the performing culture of master students.